2020
DOI: 10.3389/fonc.2020.00914
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk HPV Oncoproteins and PD-1/PD-L1 Interplay in Human Cervical Cancer: Recent Evidence and Future Directions

Abstract: Cervical cancer is the fourth most common malignancy in women worldwide and a leading cause of cancer-related mortality in developing countries. Important etiological factors in this cancer are high-risk human papillomaviruses (HPV), as roughly 96% of cervical cancer cases are positive for these oncoviruses. On the other hand, it has been recently pointed out that E6/E7 oncoproteins of high-risk HPV can upregulate the programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) axis. Likewise, several r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 105 publications
0
34
0
5
Order By: Relevance
“…We have previously shown that therapeutic vaccination with an HPV16 L2E7E6 fusion protein, TA-CIN, in the TC-1 tumor model upregulated PD-L1 on tumor cells and PD-1 on circulating CD8 1 T cells (47). Other groups have also reported that HPV-associated cancers tend to be associated with upregulated PD-L1 and enhanced responses to immune checkpoint blockades (35,(48)(49)(50). Furthermore, PD-1/PD-L1 blockade has been used in conjunction with other cancer vaccines to improve therapeutic effects (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that therapeutic vaccination with an HPV16 L2E7E6 fusion protein, TA-CIN, in the TC-1 tumor model upregulated PD-L1 on tumor cells and PD-1 on circulating CD8 1 T cells (47). Other groups have also reported that HPV-associated cancers tend to be associated with upregulated PD-L1 and enhanced responses to immune checkpoint blockades (35,(48)(49)(50). Furthermore, PD-1/PD-L1 blockade has been used in conjunction with other cancer vaccines to improve therapeutic effects (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, suppression of HOXD9 in cervical cancer can simultaneously suppress the HPV oncogenes E6 and E7, arrest cell proliferation, and induce cell death. Moreover, it has been recently pointed out that E6/E7 oncoproteins of high-risk HPV can upregulate the programmed cell death-1/programmed cell death-tligand 1 (PD-1/PD-L1) axis [33]. Upregulated levels of PD-L1 in cervical cancer are associated with poorer disease-free and disease-specific survival rates in comparison to those with normal or low PD-L1 levels [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus (HPV) is detected in more than 90% of CC cases and is considered the most important cause of cervical carcinogenesis. There are approximately 40 types of HPV that infect the female genital organs, 20 types of which, HPV16, 18,26,31,33,35,39,45,51,52,56,58,59, 66, 67, 68, 70, 73 and 82, are considered carcinogenic and classified as high-risk types [2]. HPV16 is the most frequently detected type in CC, accounting for approximately 50% of cases, followed by HPV18, accounting for 20% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cases of cervical cancer are associated with high-risk HPV (16 or 18) which encode E5, E6 and E7 proteins that drive malignant transformation. These proteins are implicated in the PD1/PDL1 pathway leading to increased PD-L1 expression [ 14 ] potentially propagating immune evasion.…”
Section: Immune Response To Cancer and Immune Checkpoint Inhibition: Rationale For Immunotherapy In Cervical Cancermentioning
confidence: 99%